Electron-Accepting π-Conjugated Compound Containing Cyano-Substituted Naphthobisthiadiazole as Nonfullerene Acceptor in Organic Solar Cells - Jinnai, Seihou; Oi, Ayumi; Seo, Takuji; Moriyama, Taichi; Minami, Ryunosuke; Higashida, Suguru; Ie, Yutaka (Synthesis, 2021)
The incorporation of electron-accepting units into π-conjugated systems can allow the modulation of the physical properties and frontier orbital energy levels of the molecules. An electron-accepting π-conjugated compound (CNNTz-TR) containing cyano-substituted naphthobisthiadiazole (CNNTz) was synthesized via a nucleophilic substitution reaction as the key step. Owing to the presence of the cyano groups, CNNTz-TR affords a low-lying lowest unoccupied molecular orbital energy level. Organic solar cells based on the blend films of CNNTz-TR and a low-bandgap donor exhibited moderate power conversion efficiencies. The results showed that embedding the CNNTz unit into the π-conjugated backbone is an effective approach for designing electron-accepting semiconducting materials.
Keywords: naphthobisthiadiazoles; organic solar cells; nonfullerene acceptors; π-conjugated molecules; organic semiconducting materials; electron-accepting unit